IFRS adoption, stock price synchronicity and volatility - Santana, Verônica de Fátima (2015)
This research aimed to investigate whether and how the adoption of the International Financial Reporting Standards (IFRS) has affected the synchronicity of stock prices in the Brazilian capital market and how this was reflected in the behavior of idiosyncratic and systematic risk. In order to do so, it was first conducted a regression analysis associating the Transition (2008 and 2009) and the Post-Adoption (from 2010) period with a measure of stock price synchronicity, controlling for structural aspects that affect the functioning of stock markets as a whole and for aspects of individual firms that affect the process of incorporating information into their stock prices and their incentives to report transparent financial statements. Then, it was built series of volatility decomposed into two components, market-wide (capturing the systematic risk) and firm-specific (capturing the idiosyncratic risk), according to the methodology of Campbell et al. (2001), and performed an analysis based on tests for identifying trends on the series. The study predicted that if IFRS was able to increase the amount of firm-specific information incorporated into stock prices, it could (i) reduce synchronicity (J. Kim & Shi, 2012), and idiosyncratic volatility would have become more intense relatively to systematic volatility; or (ii) it could increase synchronicity (Beuselinck et al., 2010; Dasgupta et al., 2010), and idiosyncratic volatility would, then, have become less intense. The results confirmed that stock price synchronicity has decreased from the Post-Adoption period, in line with the view of J. Kim & Shi (2012), that the reducing effect can be more intense for less developed countries, which tend to be more synchronous (Morck et al, 2000) and because the improvement in the informational environment acts as a substitute to the weak institutional environment. These results indicate that stock prices became more informative (Durnev, Morck, & Yeung, 2004), making the market less obscure (K. Li et al., 2003) and better able to efficiently allocate resources (Wurgler, 2000; Habib, 2008). However, although a visual analysis of the volatility series suggests a slightly upward trend for the firm-level series, the statistical tests were not able to identify any significant trend, so, only the first part of the hypothesis could be confirmed. Nevertheless, despite of this limitation and the possible caveats with the models that were used, this research provides evidence that IFRS adoption brought positive changes to the functioning of the Brazilian capital market.